Successful Management of a Gastric Leak with Endoscopic Stent after Sleeve Gastrectomy - Sang Hoon Park; Ki Nam Shim; Kang Hoon Lee; A Reum Choe; Hyeon Kyeong Jeon; Jung Won Kim; Chung Hyun Tae; Chang Mo Moon; Seong Eun Kim; Hye Kyung Jung; Sung Ae Jung; Joo Ho Lee (Yong Chan Lee, 2018)
Laparoscopic sleeve gastrectomy has become a standard procedure in bariatric surgery owing to its efficacy and simplicity. However, this procedure can cause life-threatening complications such as a gastric staple-line leak. A 24-year-old woman was transferred to the emergency department for evaluation of epigastric pain. Nine days prior to transfer, she underwent laparoscopic sleeve gastrectomy at another institution. Abdominal computed tomography (CT) revealed fluid collection with air density along the left subphrenic space and gastrosplenic ligament area. Intravenous antibiotics and total parenteral nutrition were initiated. She underwent percutaneous catheter drainage. On postoperative day 18, an esophagogastroduodenoscopy was performed to assess the site and size of the leak, and revealed a leak at the proximal staple line just below the gastroesophageal junction. A newly designed, fully covered antimigratory esophageal stent was placed to cover the leak from the distal esophagus to gastric midbody. Follow-up abdominal CT demonstrated improvement of the fluid collection at the location of the previous gastric leak. The stent was removed 3 weeks after insertion, and a barium study confirmed no more leakage. In this case, we experienced that the newly designed esophageal stent was safe and effective for preventing migration in the management of leak after laparoscopic sleeve gastrectomy.